Hubungan Peran Serta Kader dengan Pemanfaatan Sarana Alat Peraga dalam Penyuluhan Upaya Peningkatan Status Gizi Balita di Posyandu Wilayah Kerja Puskesmas Pasayangan Martapura 2013 - Akhmad Mahyuni; Rahmiyati Rahmiyati; Mastika Yanti; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2014)
The role of the cadre with the utilization of props in counseling which should be carried out by the cadres had not yet done independently and much depends on health workers, in a neighborhood health center because there are only 2 people only, while cadres according to the actual minimum number for each posyandu is 5 people. This study aims to determine relationship participation cadres with the utilization of props in counseling efforts to increase toddler nutrition status in Posyandu Work Area Public Health Center of Pasayangan Martapura in 2013. This research uses the analytical method with cross-sectional design. This research was carried out on 51 volunteers active in the IHC Public Health Center Pasayangan Martapura with simple random sampling technique. Data were collected by questionnaire and analyzed using test correlation spearman rho. The results obtained by the participation as many as 20 cadres of both (39.2%), most do not take advantage of cadres props means as many as 28 volunteers (54.9%), There was a significant correlation between the role and utilization of cadres with props in outreach efforts to improve the nutritional status of children in IHC Working Area Health Center Pasayangan Martapura year 2013 (p = 0.007). Conclusion participation posyandu most of the role and its cadres are good and most of the cadres not to utilize the facilities props so that there is a relationship role of the cadre with the utilization of visual aids in extension efforts to improve the nutritional status of children in the IHC.